PENGARUH FINANCIAL DISTRESS, FINANCIAL LEVERAGE, UMUR PERUSAHAAN DAN INFLASI TERHADAP UNDERPRICING PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO): Financial Distress, Financial Leverage, Umur Perusahaan Dan Inflasi; Underpricing - I Ketut Edi Suryawan1, I Ketut Edi Suryawan; Gede Adi Yuniarta (Universitas Pendidikan Ganesha, 2023)
The aim of this research is to examine variables that influence share underpricing when a company conducts an IPO. The underpricing phenomenon occurs due to differences in prices in the primary market as a result of an imbalance of information (information asymmetry) between the underwriter and the issuer. This condition of information asymmetry is what causes underpricing, where the underwriter is the party who has a lot of information and uses the issuer's ignorance to reduce the underwriter's risk. This price difference is known as initial return (IR) or positive return for investors. If the share price in the primary market (IPO) is lower than the share price in the secondary market on the first day, then there will be a phenomenon of low prices in the initial offering, which is called underpricing. On the other hand, if the price at the IPO is higher than the share price on the secondary market on the first day, then this phenomenon is called overpricing. This research uses quantitative methods with the research population being companies that carry out IPOs from 2020 to 2022. The sample was selected using a purposive sampling method. The research results obtained are that financial distress has no significant effect on stock underprices, financial leverage has no significant effect on stock underprices, company age has no significant negative effect on stock underprices and the inflation rate has a significant positive effect on stock underprices.